2020
DOI: 10.18276/cej.2020.1-01
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of lower extremity muscles after elite track cycling sprint events: a case report

Abstract: Sprint cycling events require a high level of anaerobic capacity and, therefore, may affect peripheral fatigue throughout exercise-induced muscle damage. In fact, those alterations might decrease power generation. This study was performed on a 23 years old male elite track cyclist taking part in a sprint event. The measurements included power output (W) and cadence (rpm), lactate concentration (La-), heart rate (bpm), Rating of Perceived Exertion scale and viscoelastic properties analysis. The present study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…Higher differences in sprinter's stiffness might be related to training specificity, e.g., short-term maximal efforts. Our previous study reported an increase in thigh muscle (especially VL) pain sensitivity after maximal anaerobic power training (Klich et al, 2018) and 200 m flying start (Klich et al, 2020). The training loads in endurance cyclists are mainly focused on aerobic capacity, and overloads does not seem to influence stiffness and thickness (Karamanidis and Arampatzis, 2006).…”
Section: Physiological Perspective To Acute and Chronic Mechanisms Fomentioning
confidence: 97%
See 4 more Smart Citations
“…Higher differences in sprinter's stiffness might be related to training specificity, e.g., short-term maximal efforts. Our previous study reported an increase in thigh muscle (especially VL) pain sensitivity after maximal anaerobic power training (Klich et al, 2018) and 200 m flying start (Klich et al, 2020). The training loads in endurance cyclists are mainly focused on aerobic capacity, and overloads does not seem to influence stiffness and thickness (Karamanidis and Arampatzis, 2006).…”
Section: Physiological Perspective To Acute and Chronic Mechanisms Fomentioning
confidence: 97%
“…Young et al ( 2018 ) have shown higher PT stiff in break-dancers compared with a control group, as a sign of adaptation after training. Klich et al ( 2020 ) found an increase in QM stiff after 200 m flying start and sprints in a case study. Among soccer players compared with healthy sedentary participants, both increased rectus femoris and lower PT and QT stiffness have been recently reported (Taş et al, 2019 ).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations